2010
DOI: 10.1111/j.1553-2712.2010.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Patient Volume and Troponin Laboratory Turnaround Time

Abstract: Objectives: Increases in emergency department (ED) visits may place a substantial burden on both the ED and hospital-based laboratories. Studies have identified laboratory turnaround time (TAT) as a barrier to patient process times and lengths of stay. Prolonged laboratory study results may also result in delayed recognition of critically ill patients and initiation of appropriate therapies. The objective of this study was to determine how ED patient volume itself is associated with laboratory TAT.Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…In contrast, evidence examining the value of typical symptoms in patients presenting with chest pain in the acute setting have demonstrated a poor correlation with the final diagnosis of acute coronary syndrome (3,(13)(14)(15)(16)(17)(18)(19). However, these studies have tended to either include patients with diagnostic ECG changes , focus on specific chest pain characteristics rather than overall typicality, or use M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 research nurses to extract this information. Although it is evident that unstructured clinical judgment or gestalt has an important role to play in the overall risk assessment of acute chest pain patients (20), the subjective interpretation of typicality of chest pain and the impact that clinical experience may have upon its diagnostic accuracy remain poorly understood.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, evidence examining the value of typical symptoms in patients presenting with chest pain in the acute setting have demonstrated a poor correlation with the final diagnosis of acute coronary syndrome (3,(13)(14)(15)(16)(17)(18)(19). However, these studies have tended to either include patients with diagnostic ECG changes , focus on specific chest pain characteristics rather than overall typicality, or use M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 research nurses to extract this information. Although it is evident that unstructured clinical judgment or gestalt has an important role to play in the overall risk assessment of acute chest pain patients (20), the subjective interpretation of typicality of chest pain and the impact that clinical experience may have upon its diagnostic accuracy remain poorly understood.…”
Section: Introductionmentioning
confidence: 80%
“…In the remainder, distinguishing whether a patient presenting with chest pain has acute coronary syndrome or a non-acute coronary syndrome problem is difficult (3). While some alternative diagnoses become apparent using history alone, the ongoing diagnostic uncertainty in the remainder of patients has been shown to lead to emergency department overcrowding, higher levels of resource use and increased healthcare costs (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, Hawkins reported that the initial goal was to complete 90% of common laboratory tests within 60 minutes (2). In 2010, the median TAT for 9492 troponin tests was 107 minutes (range 73 -148 minutes) (15). In contrast, in an Indian laboratory, the mean TAT from sample reception to report was 5.5 hours for routine inpatient samples (4).…”
Section: Discussionmentioning
confidence: 96%
“…49 Emergency department physicians also sometimes argue that longer orderto-report troponin TATs slow patients' progress to the next steps in the clinical diagnostic process, including the critical next step of cardiac catheterization. 50,51 5. The more clearly defined defect of delay beyond the anticipated interval in STAT test results' receipt-to-report times stimulates more clinician dissatisfaction.…”
Section: Connections Between Clinical Laboratory Process and Test Resmentioning
confidence: 99%
“…27,55 The clinical effect of report errors is also rare; it is easier to demonstrate for microbiology results that must be altered 55 but may also appear after erroneous chemistry results. 27,51 Rationale for the Q-Tracks Focus on Process Defects…”
Section: Connections Between Clinical Laboratory Process and Test Resmentioning
confidence: 99%